#TITLE_ALTERNATIVE# - ANGGA GINANJAR (NIM : 10211097), GIAN
Exploration is an initial stage at oil and gas field, which is started with seismic data acquisition, seismic data processing, and seismic data interpretation. Seismic reflection data has some noise signals, which are multiples, and particularly they exist in marine exploration. Multiples can interfere primary signals that give essential information and therefore giving some difficulties for interpreters in analyzing seismic reflection data. This study discuss the free-surface multiple reduction in the case of one layer of the earth, two layers of the earth, and primary signals within multiples by using inverse scattering series method. This method is a multiple reduction method, which utilizes separation method and wave prediction. Inverse scattering series method can predict the shape of free-surface multiple in the form of total reflectance value through calculation of indefinite power series. Inverse scattering series method is able to reduce the effect of free-surface multiple well at total reflectance data. Total reflectance value at free-surface multiple will decrease as wave travelling time increases. Reflectance function that has full multiples will be gone, meanwhile multiples which have primary signals will be partly gone because there is some data that indicates primary signals.